Characterization of the mineralization of the stylohyoid process in volumetric computed tomography - Benito Sifuentes, Roger (2020)
Objective: To evaluate the tomographic characteristics of the mineralization of the stylohyoid process by volu- metric computed tomography (CT). Material and Methods:  reviewed 860 volumetric computed tomographies (593 correspond to the female sex and 267 to the male sex) of the Oral and Maxillofacial Radiology Service. The age range was between 6 to 89 years. The tomographic adequacy of the Langlais classiﬁcation was used. The statistical analysis was performed using the chi-square test. Results: 289 MPE were found, bilateral mineraliza- tion prevailed (68.86%). The arithmetic average length of the MPE was 39.54 mm. The frequency of MPE was 33.60% (289 cases). It was found more frequently in the age group of 40 to 49 years, there was no signiﬁcant diﬀerence between the female and male sex (p = 0.5367). In the classiﬁcation of Langlais the most frequent type was the segmented variants with 42.2%. The most frequent MPE pattern was the partially calciﬁed variants with 58.8%. Conclusions: The frequency of the MPE was 33.60% and the TCV allows to identify this anatomical variation in a timely manner.